Pengaruh Perencanaan Pajak, Profitabilitas dan Leverage Terhadap Transfer Pricing Pada Perusahaan Platform Marketplace yang Terdaftar di BEI 2019-2022 - Pandya Aryaduta Perdana; Siti Isnaniati; Puji Rahayu (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to determine the Effect of Tax Planning, Profitability and Leverage on Transfer Pricing in Marketplace Platform Companies Registered on the IDX 2019-2022. This type of research is quantitative research. The data for this study were obtained through secondary data. The population in this study were all marketplace platform companies listed on the IDX 2019-2022. The sample in this study was 8 companies, namely 32 financial reports. The analysis techniques used were classical assumption tests, multiple linear regression analysis and hypothesis tests. The results showed that the tax planning variable (X1) had a positive and significant partial effect on transfer pricing. The ROA variable (X2) had a positive and significant partial effect on transfer pricing. The DER variable (X3) had a negative and insignificant partial effect on transfer pricing. The Tax Planning Variable (X1), ROA (X2) and DER (X3) had a positive and significant simultaneous effect on transfer pricing.